(untitled) (Bulletin KNOB, 2010)
Although a considerable percentage of the practising building historians have an academic background, the origin of building history lies in the practical preservation of monuments and historic buildings. The listing of thousands of houses around 1975 gave a strong impulse to the then new discipline. Around 1990 building history completed its pioneering phase. ‘Richtlijnen bouwhistorisch onderzoek’ (guidelines for building- historical research) created a framework for practicable research reports for the purpose of restoration. Because of social developments this discipline – which was initially strongly focused on the Middle Ages – had to widen its scope within a brief period of time. In the first instance the more recent building history from the period 1850-1940 was added. As regards the question whether the same or an adjusted method had to be adopted for it, it is argued here that the research method is not essentially different, despite the fact that the quantity and type of additional information on each building has strongly increased, if the building in its present appearance remains the central point of interest. Recently the field of research was further extended with, in the first place, more attention for the context of the building and, in the second place, greater focus on more extensive, frequently urban areas where research is taking place into the building-historical values still to be expected, which is to result in a value map.